Preserving traditional Balinese architecture: exploring the relevance of undagi’s indigenous knowledge in post-pandemic interior design - I Kadek Dwi Noorwatha; Imam Santosa (Pascasarjana Institut Seni Indonesia Surakarta, 2023)
This research is focused on exploring the relevance of undagi’s indigenous knowledge implemented on post-pandemic interior design as a recommendation for preserving traditional Balinese architecture in the modern era. As UNESCO promoted safeguarding the